Ordinance No. 13: An Ordinance in Relation to Offenses Against Public Safety, in CORNING INDEPENDENT, May 16, 1890, at 3, § 6 - (:unkn) unknown (My University, 1890)
§ 6: No person shall discharge any gun, pistol or other fire arm, except upon his own premises, and there only in proper and necessary cases. Provided, that this section shall not be so construed us to prevent any United States, State, county or city officer from discharging any firearm in the execution of his official duties.
Keywords: DISCHARGE